A matemática na robótica - Macedo, Rafael Braz de (2014)
This work has as objective shows some applications of the mathematics in the reality. He has, also the objective of answering, for the less partly the following questions: Teacher so that it serves that? Where will I use that? Because I should study that? In this work it is shown some of those applications of the mathematics so that the student knows that the mathematics is present where less if imagine. Such questions, that a lot of times are without answer, they cause incentive lack in the students, because these don’t get to see usefulness in the supplied contents. The applied mathematics is one valuable tool for who wants to see the mathematics operation. Initially an application is shown to a movable robot’s location through coordinates in the plan and measures of arches, later it will be shown a beautiful application of the so studied transformations (Algebra Lineal) and of the head offices, now applied in the space, for the movement and location of a robot manipulator’s final extremity. These applications of the mathematics are just some, because there is an infinity of other more.